Making Simple Electric Circuit with Potato: Introducing Easy DIY Science Lab Activity to Secondary School Students - Monica Prima Sari; Rani Oktavia; Rahmah Evita Putri (Fakultas MIPA Universitas Negeri Padang, 2020)
Laboratorium activity and experiment related to Dynamic Electricity topic in secondary schools have always been a “scary” thing to science teachers in Indonesia, especially to those with more experience in teaching Biology than Physics. To our surprise, the problem was more related to teacher’s confidence to conduct lab acitivy rather than to the availability of experiment kit in school. Our visit to two schools in Padang revealed that each school has sufficient amout of experiment kit for Electricity but the science teachers were too scared to take students to lab and get nervous when something is not working, or too scared to damage the kit. Therefore, we would like to offer a solution to overcome this problem by intoducing an easy do-it-yourself simpe electricity circuit with potato. The activity is expected to build more confidence in teachers to conduct lab activity and make science learning more fun to the students. Keywords — electric circuits, electricity from potato, school science, simple science experiment, dynamic electricity